Hubungan kualiti guru dengan kemenjadian murid Sekolah Rendah Tamil daerah Johor Bahru, Johor - Shanmugam, Rathidevi (2010)
The descriptive research was carried out to identify the Relationship between quality of teachers and the students achievement of the Primary Tamil School District of Johor Bahru. The Instrument used in this study was questionnaire which was designed based on aspects mention in the definite instrument of Malaysia Education Standard Quality (2003) and Malaysian Teachers Standard (2008) The study involved 194 teachers as respondents . A pilot study conducted on 20 teachers in Kluang district quality of teachers showed (coefficient reliability) aspect on professionalism value was 0.71, knowledge and capability was 0.72 and the third aspect is competency of teaching and learning was 0.82. It showed coefficient reliability of students achievement on morality aspect was 0.81, academic aspect was 0.83 and co-curriculum was 0.77. The data were analyzed using statistical Package for Social Science (SPSS Version 17) by carrying out descriptive analysis that used mean and standard deviation and inferential statistic namely t test and one way ANOVA significant of 0.05 . Findings showed that the three aspects of quality of teachers was in the high stage and students achievement was at the average stage. Findings from the t - test showed no significant differences between the teachers from Public Universities and teachers from teaching institution. Where as, findings from ANOVA showed there was no significant differences between teachers quality and professional qualification. However there was positive relationship between quality of teachers and students achievement of pupils in SJK(T) school pupils in Johor Bahru district. Based on findings of this study, several recommendations are forwarded for further enhancement of quality of teachers and the achievement of primary Tamil School. This need special attention from the administration in the future.